The effectiveness of risk management: a case study of CTRM Aero Composites / Azni Nur Kamilah Shahar - Shahar, Azni Nur Kamilah (Faculty of Business and Management, 2011)
CTRM AC is entrusted with a strategic role to develop high technology based industry, namely the aerospace and composites industries. In line with this vision, CTRM started it business operations with the assemblies and manufacturing of a two-seater composites light aircraft, Eagle 150B. Today, CTRM is part of the global supply chain composites aero structures for major commercial and military aircraft manufacturers in the world. The increasing level awareness of the important for Risk Management, finally CTRM AC decides to build up a team of Risk Management or we call it as Risk Management Department (RMD). The main functions for this department to handle the risk that are strongly belief exist in CTRM AC and need to be figure out. However, its implementation is much more complex in practice. Established in 2007, Risk Management experienced many achievement and problems. The major findings of this research found that the functions performed by Risk Management Team having few problems and need to be monitor to improve and reach the objective for year 2011 to achieve Level 3 in maturity level.